Modeling orthogonal and rectilinear mixed-modality projection of optical tomography for solid-particles concentration measurement - Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Goh, C. L.; Rahim, H. A.; Yunos, Y. M.; Muji, S. Z. M. (Elsevier B. V., 2010)
Link to publisher's homepage at http://www.elsevier.com/